Do Migrants Send Remittances as a Way of Self-Insurance? Evidence from a Representative Immigrant Survey - Catia Batista; Janis Umblijs (Institute for the Study of Labor (IZA), 2014)
Do migrants send remittances as a way of obtaining insurance? While this motive is theoretically suggested in the literature, the question of identifying this relationship empirically has only begun to be explored. Using a unique representative survey of 1500 immigrants in the Greater Dublin Area, Ireland, we find a positive and significant relationship between risk aversion and remittance behavior. Risk-averse individuals are more likely to send remittances home and are, on average, likely to remit a higher amount, after controlling for a broad range of individual and group characteristics. Consistent with a purchase of self-insurance motive to remit, we also provide evidence of more remittances sent by risk averse immigrants facing higher wage risks and remitting to individuals with more financial resources.
Keywords: D81; F22; F24; J01; J08; J15; J61; 330; migration; risk aversion; remittances; insurance